Atribusi Personal dan Pengalaman Agresif sebagai Prediktor Perilaku Agresif Siswa - Syamsul Bachri Thalib (Universitas Negeri Malang, 2016)
This study focuses on topics of behavioral aggressiveness conducted in The US, Canada, England, Finland, Dutch, Hongkong, and Indonesia. Utilizing 33 studies published between 1992 and 1999 this meta-analysis specifically examines the relation between the personal attribution and experiences aggression with aggressive behaviors. The subjects include 6967 persons with different ages, educational levels, and job status. The results indicate that there is a positive relation between personal attribution and aggressive behavior and between experience of aggression and aggressive behaviors. This meta-analysis supports the conclusion in the current literature